Error analysis and control scheme for the error correction in trajectory-tracking of a planar 2PRP-PPR parallel manipulator. (October 2017) - Mohan, Santhakumar
Highlights: Motion accuracy of a planar 2PRP-2PPR parallel manipulator is investigated. A robust end-effector pose error correction control scheme is also proposed. The proposed control scheme is a dual-loop control scheme. It corrects the joint space positions based on task-space measurements. The proposed control scheme is simple and easy to use. Abstract: This paper presents the end-effector pose error modeling and motion accuracy analysis of a planar 2PRP-PPR parallel manipulator with an unsymmetrical (U-shape) fixed base. The error model is established based on the screw theory with considerations of both configuration (geometrical) errors and joint clearances. It also proposes a robust cascaded control scheme for the end-effector pose (task-space) error correction in trajectory-tracking of the manipulator due to mechanical inaccuracies. The proposed control scheme uses redundant sensor feedback, i.e., individual active joint displacements and velocities and, end-effector positions and orientation are obtained as feedback signals using appropriate sensors. To demonstrate the efficacy and show complete performance of the proposed controller, real-time experiments are accomplished on an in-house fabricated planar 2PRP-PPR parallel manipulator.